2016
DOI: 10.11113/ijbes.v3.n2.126
|View full text |Cite
|
Sign up to set email alerts
|

The Success Criteria of Public Housing Project in Nigeria

Abstract: There is no consensus among researchers of what constitutes projects success; every project type may have different success criteria. Identifying project success criteria at the initial stage of a project can contribute to effective utilization of resources. The aim of this study is to establish the criteria for measuring public housing project success in Nigeria. The data collection was carried out in Nigeria by means of structured interviews with ten experts in housing, a pilot survey and questionnaire surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…This copes with the above stated author's personal experience. Frefer et al (2018) compare the findings of Pinto and Slevin (1988) on projects' critical success factors with other researchers' conclusion (Freeman and Beale, 1992;Khosravi and Afshari, 2011;Bryde and Robinson, 2005;Bahia and de Farias Filho, 2010;Al-Tmeemy et al, 2010;Mukhtar and Amirudin, 2016;Gomes and Romão, 2016;Omer, 2017), shown in adapted Fig. 2.…”
Section: Literature Reviewmentioning
confidence: 95%
“…This copes with the above stated author's personal experience. Frefer et al (2018) compare the findings of Pinto and Slevin (1988) on projects' critical success factors with other researchers' conclusion (Freeman and Beale, 1992;Khosravi and Afshari, 2011;Bryde and Robinson, 2005;Bahia and de Farias Filho, 2010;Al-Tmeemy et al, 2010;Mukhtar and Amirudin, 2016;Gomes and Romão, 2016;Omer, 2017), shown in adapted Fig. 2.…”
Section: Literature Reviewmentioning
confidence: 95%
“…According to Mukhtar and Amirudin (2016) equally, the purpose of public housing projects is to assist low income earners who cannot compete on a market place to own or have access to decent housing. Public housing has therefore been simply described as government-provided or subsidized housing project(s) whose objective is to make decent housing available for households who cannot access it at market conditions and prices.…”
Section: Public Housingmentioning
confidence: 99%
“…This connotes public housing delivery being processed to a better position for the achievement of its purpose. Mukhtar and Amirudin (2016) opine that if the purpose of a public housing project is not achieved, it is then regarded as unsuccessful, in other words inefficient. Put together, efficiency of public housing products involves the provision of necessary amenities to make government housing delivery available for those households who cannot access it at market conditions and prices functional, convenient, aesthetically pleasing, safe and hygienic (Ibimilua & Ibitoye, 2015).…”
Section: Efficiency Of Public Housing Products' Performancementioning
confidence: 99%
See 1 more Smart Citation
“…To improve the chances of building project success and reduce the possible failures, the performance criteria for BPM practices should be properly and carefully identified, measured, and checked. It has been observed that time, cost, quality, health and safety, environment, productivity, risk management, human resource and client satisfaction, among others, are dominant critical success factors reported by construction projects (Omer, 2017;Bryde & Robinson, 2005;Ramlee et al, 2016;Takim & Akintoye, 2002;Bahia & de Farias Filho, 2010; Al-Tmeemy, Abdul-Rahman & Harun, 2010; Koelmans, 2004;Gunathilaka, Tuuli & Dainty, 2013;Frefer et al, 2018;Homthong & Moungnoi, 2016;Gomesa & Romao, 2016;Toor & Ogunlana, 2010;Enshassi, Mohamed & Abushaban, 2009;Mukhtar & Amirudin, 2016). Studies by Homthong and Moungnoi (2016) revealed the most critical success factors influencing project success to include the competence of project participants, the durability of the completed work, the relationship between project participants, positive attitude of employees, effective quality assurance system in the organisation, quality of works to match standards, the relationship between an employee and a supervisor, competent supervisors and regular maintenance of equipment for the project.…”
Section: Critical Success Factorsmentioning
confidence: 99%